Perancangan Motion Graphic Isometrik 2D Sebagai Edukasi terhadap Dampak Bahaya Pinjaman Online Ilegal untuk Guru - Felix Dwi Natanael; Jason Prestiliano; T. Arie Setiawan Prasida (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
The rapid advancement of technology has made it easier for the public to access online loans (pinjol), but it has also increased the risk of misuse by illegal entities. The Financial Services Authority (OJK) recorded that from 2018 to 2022, it shut down 4,265 illegal online lending platforms. However, many cases continue to emerge due to the ease of creating applications and the use of overseas servers. Teachers are among the most affected victims due to low salaries and high living costs. The impacts of illegal online loans are highly detrimental, including the leakage of personal data, threats, intimidation, and excessively high interest rates. Education is crucial to prevent new victims. Isometric motion graphics are chosen as a medium because of their advantages in delivering information through engaging, clear, and easily understood visual and audio elements that are sustainable for audiences.